EFL Students’ Interpretations of E-Learning during COVID-19 using GETAMEL: Indonesian Higher Education Context - Yulianto, Dedy; Setyaningsih, Endang; Sumardi, Sumardi (Register Journal, 2021)
While the use of e-learning has been around for decades, the global pandemic increased the number of investigations on e-learning exponentially. Earlier studies have given useful insights into the benefits/ impacts of e-learning. However, students’ acceptance of technology within the context of emergency EFL remote teaching is still under-researched. A qualitative study framed within the General Extended Technology Acceptance Model for E-Learning (GETAMEL) aims to shed light on the students’ acceptance of technology during pandemics based on their perceived experience. It reports the challenges, opportunities of e-learning, and projections on future use based on the current experience. To collect the data, a questionnaire consisting of open and closed questions was distributed to 89 participants. In-depth interviews were conducted with focal respondents after gaining their consent. The data were then analyzed using the interactive model of data analysis. This study reveals that regardless of the negative experiences and challenges in the use of technology in e-learning, the students held positive perspectives and saw opportunities to use technology during the COVID-19 pandemic. They projected their future practice using the technology. These indicate that the students well accept the use of technology in the e-learning context. The study concluded that using e-learning during a pandemic is the ideal way to continue learning. However, given the challenges that students face, some changes in the implementation of distance learning are still needed. Additional studies should address GETAMEL on EFL teachers in an Indonesian school, so we know about the acceptance of e-learning by in-service teachers.Keywords: COVID-19, EFL students, e-learning, GETAMEL, higher education